Puntos clave en el tratamiento de la dermatitis en Latinoamérica. El Consenso SLAAI (2015)
ABSTRACT: The incidence of atopic dermatitis in Latin America, as in other regions, has been increasing in recent years. The SLAAI consensus is based on a systematic search for articles related to dermatitis, with focus in the pathophysiology and treatment and its impact on Latin America, and reviewed using the Delphi methodology (Revista Alergia Mexico 2014;61:178-211). In this article we highlight the key points of consensus and particular considerations in Latin America.